Effect of different helmets against ground impact based on the in-depth reconstruction of electric two-wheeler accidents. Issue 4 (12th March 2023) - Han, Yong; He, Yong; Pan, Di; Lin, Liya; Chen, Yisheng; Feng, Hao
Abstract: Skull fracture and brain injury are frequent head injuries in electric two-wheeler (ETW) accidents, and the type of helmet and impact conditions affect the effectiveness of the helmet in protecting the rider's head. The purpose of this study was to conduct in-depth reconstructions of rider's head-to-ground impacts in ten ETW accidents by using a multi-body system combined with a finite element approach and to evaluate the effect of two typical full-face helmets (FFH) and one half-coverage helmet (HCH) through head accelerations and intracranial biomechanics injury metrics in ground impacts. The results showed that all three helmets reduced the risk of skull fracture in most cases, however, FFH performed better due to its wider protection area. In addition, three helmets showed varying degrees of overall reduction in measuring all indicators of brain injury. Although the effectiveness of the helmets on angular acceleration was largely influenced by the angle and location of impact, it was certain that wearing an FFH was more likely to reduce rotational head movements than an HCH, and that the FFH also offered the better advantage in reducing diffuse axonal injury (DAI) risk due to its better resistance to ejection in a crash.